Effects of EU GSP agreement on Philippine exports : 1987-2015 - DUMAG, DARRYL (Archīum Ateneo, 2018)
The Generalized System of Preferences (GSP) is a preferential trade scheme that provides duty-free treatment on the goods determined by advanced economies to support developing countries' economic growth. Using the theoretical framework of Viner (1950) and Grossman and Sykes (2005), and the empirical model of Gabrielsson-Kjäll and Ädel (2010), the study analyzes the impact of the European Union's GSP (EU GSP) on Philippine exports to EU using the gravity empirical model. The period of analysis is from 1987 to 2015. Regression estimates reveal that EU GSP has increased the value of Philippine exports to EU by $124,000. Estimation shows that the coefficients of importing countriesf GDP, dummy variables EU GSP and FTA are positive and significant. The findings confirmed that the EU GSP created trade between the Philippines and EU.